Pengawasan DPRD Provinsi Riau Dalam Pengelolaan APBD Provinsi Riau Tahun 2024 - Rahmadhani, Nadya; Febrian, Ranggi Ade (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine and describe the Supervision of the Riau Provincial DPRD in Managing the Riau Provincial APBD in 2024. Supervision indicators include: Direct Supervision and Indirect Supervision. The researcher uses a qualitative and descriptive research approach. Key Informants: Chairperson of the Riau Provincial DPRD, Informants: Commission of the Riau Provincial DPRD, Members of the Riau Provincial DPRD Budget Agency, Riau Provincial Bappeda, Riau Provincial BPKAD The types and techniques of data collection used consist of primary data collected using interview techniques, and secondary data collected using observation techniques. Data analysis consists of four simultaneous activity flows, namely, Data collection, data reduction, data presentation, drawing conclusions/verification. Research Results: Riau Provincial DPRD Supervision of the APBD is carried out through two methods, namely: Direct supervision, such as field inspections, on-site observations, and visit reports. Indirect supervision, such as written reports, meeting recommendations, and oral submissions in official forums. Supervision has been running, but is not optimal because: Documentation is not comprehensive, Coordination between commissions and DPRD equipment is lacking, Not all recommendations are followed up by OPDs. Increase HR capacity and special time for supervision, including technical training for DPRD members. Build an integrated digital system so that the DPRD can monitor budget realization in real-time. Encourage the executive to take DPRD recommendations seriously, by building a monitoring mechanism for OPD follow-up.